Difference of calcium levels in Javanese, Madurese, and Chinese preeclamptic women - Nuzulul Azizah Ramdan Wulandari; Ernawati Ernawati; Muhammad Ilham Aldika Akbar (Majalah Obstetri dan Ginekologi, 2017)
Objectives: To analyse difference of calcium levels and charac-teristics between Javanese, Madurese, and Chinese pre-eclamptic women that affects preeclampsia incidence.Materials and Methods: This was a cross-sectional study with preeclamptic patients in Dr. Soetomo Hospital, Dr. M. Soewan-dhie Hospital, and Universitas Airlangga Hospital as sample. Sample was taken by measuring total calcium level in blood serum before receiving MgSO4 using in vitro clinical chemical dimension method in the Laboratory of Clinical Pathology in Dr. Soetomo Hospital. Sample was taken using consecutive sampling. Sample size 53 preeclamptic women as participants of this study, divided into three groups of Javanese, Madurese, and Chinese.Results: There were 53 preeclampsia patients, with mean ages: Javanese 31.21±5.76, Madurese 34.20±5.58, and Chinese 28.20 ±2.16. Mean BMI: Javanese 31.19±5.99, Madurese 27.66±4.74, and Chinese 26.24±2.13. We found significant difference in total calcium levels. In Madurese it was 7.7 mg/dL, Javanese was 8.3 mg/dL, and Chinese was 9.0 mg/dL (p=.000).Conclusion: The highest severity of preeclampsia was in the Madurese with low calcium levels. The lowest the calcium level, the worst the severity of the preeclampsia.